Pharmaceutical drug two-warehouse inventory model under FIFO dispatching policy using ant colony optimization for travelling salesman problem - Yadav, Ajay Singh; Sharma, Veenita; Agarwal, Priyanka; Swami, Anupam; Yadav, Piyush Kumar (Linguistics and Culture Review, 2021)
In this paper a deterministic Pharmaceutical drug inventory model for deteriorating items with two level of storage system and time dependent demand with partial backlogged shortages is developed. Stock is transferred RW to OW under bulk release pattern and the transportation cost is taken to be negligibleUnder FIFO dispatching policy Using Ant Colony Optimization for travelling salesman problem. The deterioration rates in both the warehouses are constant but different due to the different preservation proceduresUnder FIFO dispatching policy Using Ant Colony Optimization for travelling salesman problem. Holding cost is considered to be constant up to a definite time and is increases. Ant Colony Optimization for travelling salesman problemwith varying population size is used to solve the model. In this Ant Colony Optimization for travelling salesman problem a subset of better children is included with the parent population for next generation and size of this subset is a percentage of the size of its parent set.The numerical example is presented to demonstrate the development of mode land to validate it. Sensitivity analysis is performed separately for each parameter and Ant Colony Optimization for travelling salesman problem.